2020
DOI: 10.1101/2020.11.11.379214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rothmund-Thomson Syndrome-like RECQL4 truncating mutations cause a haploinsufficient low bone mass phenotype in mice

Abstract: Rothmund-Thomson Syndrome (RTS) is an autosomal recessive disorder characterized by poikiloderma, sparse or absent hair, and defects in the skeletal system such as bone hypoplasia, short stature, low bone mass, and an increased incidence of osteosarcoma. RTS type 2 patients typically present with germline compound bi-allelic protein-truncating mutations of RECQL4. As existing murine models predominantly employ Recql4 null alleles, we have here attempted to more accurately model the mutational spectrum of RTS b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
1
0
1
Order By: Relevance
“…Indeed, dysregulation of RECQL4 is associated with several human cancers (59). Moreover, a recent study proposed that mice with RECQL4 truncating mutations do not exhibit tumorigenesis even after exposure to ionizing radiation (60), which suggested that RECQL4-deficiency might play an important role in protecting against deleterious effects later in life in mammals (Figure 7B). Further studies are needed to determine whether this effect is also observed in other RECQL4-deficient mice or patients with RTS.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, dysregulation of RECQL4 is associated with several human cancers (59). Moreover, a recent study proposed that mice with RECQL4 truncating mutations do not exhibit tumorigenesis even after exposure to ionizing radiation (60), which suggested that RECQL4-deficiency might play an important role in protecting against deleterious effects later in life in mammals (Figure 7B). Further studies are needed to determine whether this effect is also observed in other RECQL4-deficient mice or patients with RTS.…”
Section: Discussionmentioning
confidence: 98%
“…Suele iniciar con un eritema malar en el primer trimestre de vida, que se extiende hacia las extremidades, respetando tronco y abdomen; con el tiempo, toma la forma usual de las lesiones cutáneas como hiperpigmentaciones marrones violáceas que rodean zonas hipopigmentadas, siendo esto un patrón reticular. Se presentan telangiectasias permanentes, predominantes en las mejillas (4,6). En ocasiones, puede acompañarse de ampollas que suelen progresar a úlceras, sobre todo en las manos.…”
Section: Revisión De La Literaturaunclassified